2011
DOI: 10.1002/pssr.201105463
|View full text |Cite
|
Sign up to set email alerts
|

Study of detached back reflector designs for thin‐film silicon solar cells

Abstract: We present a precise and flexible method to investigate the impact of diverse detached reflector designs on the optical response of p–i–n thin‐film silicon solar cells. In this study, the term detached reflectors refers to back reflectors that are separated from the silicon layers by an intermediate rear dielectric of several micrometers. Based on the utilization of a highly conductive n‐doped layer and a local electrical contact scheme, the method allows the use of non‐conductive rear dielectrics such as air … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 10 publications
0
16
0
Order By: Relevance
“…All solar cells have poor conversion efficiency for wavelengths near the active-layer bandgap, motivating many previous light-management studies for non-heterojunction silicon devices. 6,7,[9][10][11][12][13][14][15][16] However, IR light management in silicon heterojunction solar cells is neither like that in diffused-junction crystalline silicon solar cells nor like that in thin-film silicon cells. Heterojunction cells and monocrystalline diffused-junction cells share the same random pyramid texture at the silicon surfaces, so that the angular distribution of light paths-and thus the probability of absorption in the wafer or escape out the front-is similar in both devices in the absence of parasitic absorption.…”
Section: Introductionmentioning
confidence: 99%
“…All solar cells have poor conversion efficiency for wavelengths near the active-layer bandgap, motivating many previous light-management studies for non-heterojunction silicon devices. 6,7,[9][10][11][12][13][14][15][16] However, IR light management in silicon heterojunction solar cells is neither like that in diffused-junction crystalline silicon solar cells nor like that in thin-film silicon cells. Heterojunction cells and monocrystalline diffused-junction cells share the same random pyramid texture at the silicon surfaces, so that the angular distribution of light paths-and thus the probability of absorption in the wafer or escape out the front-is similar in both devices in the absence of parasitic absorption.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a metallic BR, parasitic absorption usually occurs in the metal because of texture-mediated or roughness-mediated plasmonic interactions [19][20][21]. It has been shown that a dielectric layer with a low refractive index inserted between the silicon layers and the metal reduces the plasmonic losses in the metal layer [19,20,[22][23][24][25][26]. Most commonly, an~100-nm-thick layer of sputtered aluminum-doped ZnO or of sub-stoichiometric silicon oxide is combined with an opaque Ag layer [1][2][3][4][5][6][7][8]27,28].…”
Section: Introductionmentioning
confidence: 99%
“…The strong and simultaneous increase in the absorptance, of 5.4% and 9.1% at 750 nm, indicates that the enhancement of the EQE is mainly caused by an improvement of the light trapping in the active layer of the solar cell rather than an enhanced reflectivity of the BR. More details about this explanation are given in Reference [21]. The improvement of the light-trapping properties for lower n rd is confirmed by the significant enhancement of the Haze, measured in the reflection mode of the complete solar cell (not shown).…”
Section: Experimental Results In the Particular Case Of A Flat Ag Bacmentioning
confidence: 64%
“…Despite this result, the highest optical cell performance obtained so far by our group was found by using a detached textured Ag BR in combination with air as a rear dielectric. This BR design was found to outperform the commonly used 80 nm‐ZnO/Ag BR design and even a 110 nm‐SiO 2 /Ag BR design, showing noticeably reduced parasitic losses . In the long wavelength range ( λ > 800 nm), the experimental results show a significantly reduced cell absorptance with air as a rear dielectric rather than with a thin layer of SiO 2 .…”
Section: Resultsmentioning
confidence: 80%